Shan-chien-pʻi-pʻo-sha; a Chinese version by Saṅghabhadra of Samantapāsādikā, commentary on Pali Vinaya - Saṅghabhadra, fl. 489-502 (Bhandarkar oriental series, 1970)
Theravada Buddhist monastic discipline (vinaya); Chinese version of a commentary on the Vinaya by Buddhaghosa.